KECERDASAN EMOSIONAL (EMOTIONAL QUOTIENT) DALAM PENINGKATAN PRESTASI BELAJAR - Andriani, Asna (EDUKASI: Jurnal Pendidikan Islam, 2014)
During this time many people have an opinion that everyone needs an Intellectual Quotient (IQ) to reach an achievement in their live, but today according to a research product in psychology field gives an evidence that not only an Intellectual Quotient (IQ) but also there is the other factor which influences an achievement or a successful in the future. Its named an Emotional Quotient (EQ) which has means a personÃ¢â¬â¢s capability for managing and motivating his emotion, and interlacing the relationship with others. So that we can say that EQ is a foundation of reaching achievement for the student in their studying. This papper will discusse about the influence of Emotional Quotient (EQ) towards studentÃ¢â¬â¢s achievement in their live. There fore the parents, teachers, and counselors hopped to know and apply it for their sons, daughters, students, and cliens, in order that they can reach a good achievement in their school and more to be successful in their future.